The effect of a worksite based walking programme on cardiovascular risk in previously sedentary civil servants [NCT00284479] - Hare Lesley G; Boreham Colin AG; Murtagh Elaine M; Murphy Marie H; Nevill Alan M (BMC, 2006)
Abstract Background A significant proportion of Europeans do not meet the recommendations for 30 mins of physical activity 5 times per week. Whether lower frequency, moderate intensity exercise alters cardiovascular disease (CVD) risk has received little attention. This study examined the effects of 45 minutes self-paced walking, 2 d· wk-1 on aerobic fitness, blood pressure (BP), body composition, lipids and C-Reactive Protein (CRP) in previously sedentary civil servants. Methods 37 subjects (24 women) aged 41.5 ± 9.3 years were randomly assigned to either two 45 minute walks per week (walking group) or no training (control group). Aerobic fitness, body composition, blood pressure (BP), CRP and lipoprotein variables were measured at baseline and following 8 weeks. Steps counts were measured at baseline and during weeks 4 and 8 of the intervention. Results Compared to the control group, the walking group showed a significant reduction in systolic BP and maintained body fat levels (P < 0.05). There were no changes other risk factors. Subjects took significantly more steps on the days when prescribed walking was performed (9303 ± 2665) compared to rest days (5803 ± 2749; P < 0.001). Conclusion These findings suggest that walking twice per week for 45 minutes at ~ 62% HRmax, improves activity levels, reduces systolic BP and prevents an increase in body fat in previously sedentary adults. This walking prescription, however, failed to induce significant improvements in other markers of cardiovascular disease risk following eight weeks of training.